Orai1‐induced store‐operated Ca2+ entry enhances phospholipase activity and modulates canonical transient receptor potential channel 6 function in murine platelets. (April 2014) - Chen, W.; Thielmann, I.; Gupta, S.; Subramanian, H.; Stegner, D.; van, R.; Dietrich, A.; Gambaryan, S.; Heemskerk, J. W. M.; Hermanns, H. M.; Nieswandt, B.; Braun, A.
Summary Background Orai1, the major store‐operated Ca2+ entry (SOCE) channel in platelets, is not only critical for enhancing diverse signaling pathways, but may also regulate receptor‐operated Ca2+ entry (ROCE). Dynamic coupling of the Orai1 signalosome to canonical transient receptor potential channels (TRPCs) has been suggested as an essential step in the activation of SOCE and ROCE. However, the functional significance of the biochemical interaction between Orai and TRPC isoforms remains controversial. Objective We aimed to elucidate the role of Orai1 in diacylglycerol (DAG)‐mediated ROCE. Methods Trpc6 −/− , Orai1−/− and Orai1−/−/Trpc6−/− mice were generated, and their platelets were analyzed. Results Thapsigargin (TG)‐induced SOCE was further reduced in Orai1−/−/Trpc6−/− platelets as compared with Orai1−/− platelets, thus revealing that TG‐induced signaling pathways can activate TRPC6. Thapsigargin‐induced SOCE leads to enhanced phospholipase C and D activity in wild‐type platelets. The activity of both enzymes was significantly reduced in Orai1−/− platelets upon TG stimulation, whereas receptor‐induced phospholipase activity was not affected. Furthermore, TG‐induced and glycoprotein VI‐mediated thromboxane A2 release was strongly dependent on Orai1‐mediated SOCE. Conclusion The regulation of TRPC6 activity can occur independently of the physical interaction with Orai1. TRPC6 operates in crosstalk with Orai1 through Orai1‐induced DAG production via phospholipase activation. Orai1‐induced DAG production and thromboxane release amplify the second phase of Ca2+ signaling in platelets.